2015
DOI: 10.1158/2159-8290.cd-14-0921
|View full text |Cite
|
Sign up to set email alerts
|

The p53 Target Gene SIVA Enables Non–Small Cell Lung Cancer Development

Abstract: Although p53 transcriptional activation potential is critical for its ability to suppress cancer, the specific target genes involved in tumor suppression remain unclear. Siva is a p53 target gene essential for p53-dependent apoptosis, although it can also promote proliferation through inhibition of p53 in some settings. Thus, the role of SIVA in tumorigenesis remains unclear. Here, we seek to define the contribution of SIVA to tumorigenesis by generating Siva conditional knockout mice. Surprisingly, we find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…Consistent with this pro-tumorigenic role for Siva1, a higher level of SIVA1 expression correlated with reduced NSCLC patient survival. 15 These data also support the notion that SIVA1 can be an adverse prognostic factor for AML (Figure 2h). …”
supporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with this pro-tumorigenic role for Siva1, a higher level of SIVA1 expression correlated with reduced NSCLC patient survival. 15 These data also support the notion that SIVA1 can be an adverse prognostic factor for AML (Figure 2h). …”
supporting
confidence: 81%
“…Indeed, conditional knockout of SIVA1 inhibited tumorigenesis in KRAS-driven non-small cell lung cancer (NSCLC) mouse model, suggesting that Siva1 facilitates tumorigenesis. 15 Similarly, SIVA1 knockdown in both mouse and human NSCLC cell lines decreased proliferation and transformation. Consistent with this pro-tumorigenic role for Siva1, a higher level of SIVA1 expression correlated with reduced NSCLC patient survival.…”
mentioning
confidence: 98%
“…In leukemia cell lines, SIVA1 also binds to and inhibits Stathmin 1 activity, preventing tumor growth [20]. In contrast to the tumor suppression functions initially described for SIVA, recent studies indicate that the conditional knockout of SIVA1 reduced tumorigenesis in KRAS-driven lung cancer murine model [21] and high SIVA1 expression was associated with worse survival rates in AML patients [22]. In the present study, we characterized SIVA1 and SIVA2 expressions in healthy controls and MDS patients, and their correlation with clinical features, as well as the expression of SIVA-related genes: TP53 and MDM2.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the answer will lie in the identification of novel p53 targets. In this issue of Cancer Discovery the authors, Van Nostrand et al, focus on a novel p53, target gene, SIVA, that has been shown to play a critical role in apoptosis (5). Unlike other such target genes, it has a counterintuitive p53 independent role as a tumor promoter in the context of a non-small cell lung carcinoma (NSCLC) driven by the KRAS G12D mutation.…”
mentioning
confidence: 99%
“…The authors have chosen to examine the effects of SIVA knock-down in oncogenic KRAS-driven NSCLC development using a mouse model (5). NSCLC cells have a wild-type p53 that has been shown to suppress malignant progression.…”
mentioning
confidence: 99%